Nonadherence to antiretroviral therapy in HIV-positive patients in Costa Rica. - Stout, Brian Douglas; Leon, Maria Paz; Niccolai, Linda M (AIDS patient care and STDs, 2004)
A cross-sectional study was performed among seropositive individuals who sought HIV treatment at an outpatient clinic in San Jose, Costa Rica, to determine the prevalence, predictors, and reasons for nonadherence to antiretroviral. A structured, face-to-face interview was administered to 88 patients. The primary outcome of adherence was measured as taking 100% of medications within 3 days prior to interview. A number of risk factors, including demographic information, HIV knowledge, logistics of the regimen, and management skills were assessed. Statistical analyses included logistic regression. Eighty-five percent of patients took 100% of their medications in the last 3 days. Factors that were correlated with nonadherence included difficulty in finding transportation to the clinic (odds ratio [OR] = 6.3, p = 0.01), not laying pills out as a management skill (OR = 9.9, p = 0.01), and prescription instructions to take medication on an empty stomach (OR = 6.7, p = 0.03). HIV-positive patients in this Costa Rican sample were fairly adherent to their drug regimens. To increase adherence among non-adherent individuals, interventions that increase access in remote areas and help people manage their regimens may be beneficial.
Keywords: Adolescent; Adult; Aged; Anti-HIV Agents; CD4 Lymphocyte Count; Costa Rica; Cross-Sectional Studies; Female; Health Knowledge, Attitudes, Practice; Health Services Accessibility; HIV Seropositivity; Humans; Logistic Models; Male; Middle Aged; Motivation; Needs Assessment; Outpatient Clinics, Hospital; Patient Compliance; Patient Education as Topic; Prevalence; Questionnaires; Risk Factors; Transportation